RETRACTED: Integrated knowledge exploitation: The complementarity of product development and technology licensing - Lichtenthaler, Ulrich; Ernst, Holger (Strategic Management Journal, 2012)
Abstract In light of increasing licensing, we challenge the common assumption that product development and technology licensing are substitutes. We develop a resource‐based framework, which distinguishes a firm's technological resource base and technology exploitation processes. We further combine survey, patent, and financial data of 228 medium‐sized and large industrial companies to examine the interactions of firms' product development processes and technology licensing processes in order to explain heterogeneity in new product revenues, licensing performance, and firm performance. The results underscore that product development, which indicates innovative capacity, and technology licensing, which indicates desorptive capacity, are complements rather than substitutes in integrated knowledge exploitation in medium‐sized and large firms. This complementarity is particularly pronounced in firms with an emphasis on cross‐licensing and with a strong patent portfolio. Copyright © 2012 John Wiley & Sons, Ltd.